Pengaruh Bauran Pemasaran, Pelayanan Terhadap Keputusan Pembelian Telepon Seluler (Studi Kasus Toko Bina Mitra Usaha Desa Cipari Makmur) - Muniroh, Muniroh; Sabtohadi, Joko; Abdullah, Rahim (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:The purpose of this research is to know variable influence the product , the price of , and services of the decision of the purchase , either simultaneously or partial .The study is done in the form of survey , by adopting both explanation reseach .Variable products , have a negative influence insignificant of the decision of the purchase .While variable prices and service significant have had a positive impact of the decision of the purchase .Then the product , the price of , and services jointly significant on variables customer satisfaction .Â Keywords; The Product, The Price, Service, Decision The Purchase